State Internally Generated Revenue and Human Capital Sustainability; A case Study of Lagos State - TITILAYO OWOLABI; ADEKUNLE ADEFISOYE; TAJUDEEN BUSARI (CV ODIS, 2022)
Sustainability concept should be one of the watchwords in public sector when it comes to the provision of social amenities to the citizen as it enhances more quality services. Provision of qualitative education and ensuring that the citizens have access to learning in a conducive environment is one of the major function of the state governments in Nigeria. Sustainability of education can only be achieved through the proper management of the internally generated revenue (IGR) by each state in the country. This study examined how the internally generated revenue has contributed to the human capital development and its sustainability. The human capital development is measured using capital expenditure incurred on education in Lagos state from 2000-2020. For the purpose of this study education is used as the proxy for human capital development. This study employed ex-post factor research design. Population and sample size comprised the entire IGR and capital expenditures on education sector by Lagos state government from year 2000-2020. Audited financial statements of the state for the periods were gathered from the office of the Accountant General of the state. The data were analyzed using correlation and Ordinary Least Square regression method. The findings showed that the internally generated revenue has a significant positive effect on the sustainability of education in Lagos state while other internally generated revenue like fees and fines imposed by the state government has an insignificant negative impact on the sustainability of education in the state. In conclusion, it was gathered that Lagos state has been efficient in the utilization of its IGR towards the sustainability of education in the state. The study recommended that education sustainability should be recognized as an integral part of Human Capital Development and Sustainability Goal of all the states in Nigeria. Keywords: Sustainability, education, internally generated revenue, capital expenditure, human capital development.